SISTEM PENDETEKSI KULIATAS AIR MINUM ISI ULANG MENGGUNAKAN SENSOR PH BERBASIS INTERNET OF THINGS PADA TOKO SUPER JENIH - Sahida, Nirmala; Zaenudin; Muhamad Masjun Efendi; Lalu Delsi Samsumar (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The development of Internet of Things (IoT) technology provides great opportunities in managing the quality of refill drinking water which requires real-time monitoring to ensure quality that is suitable for consumption. In the city of Mataram, the Super Jernih water depot faces the challenge of a lack of water quality detection equipment which can reduce public confidence. This research aims to design and implement a water quality monitoring system using an IoT-based pH sensor connected to the Blynk application as a user interface. The method used is prototyping, which involves the stages of needs analysis, design, prototype development, as well as system evaluation and improvement. The research results show that this system is successful in detecting water quality accurately, providing information regarding the suitability of drinking water through the pH value displayed in real-time on the Blynk and LCD applications. Testing shows that the system functions as expected and can increase public confidence in the quality of refillable drinking water. This system is a practical and efficient solution in ensuring water quality standards that are suitable for consumption.